Upaya Penguatan Eksistensi Depo Pemasaran Ikan Sidoarjo melalui Branding dan Promosi - Sandria, Fasa; Shabira, Zahra; Fitrianah, Listin; Khasan, Muhammad Abidil; Nugraha, Taufiq Aditya; Putra, Surya Adi; Aulina, Nida; Tristanti, Elma Aprilia (Journal of Science and Social Development, 2024)
Many people in Sidoarjo do not know about the Sidoarjo Fish Marketing Depot. People better know the fish marketing depot from outside the Sidoarjo area.This service aims to strengthen the existence of the Sidoarjo Fish Marketing Depot, especially for the people of the Sidoarjo area itself through digital branding. The method used in this study is a descriptive qualitative approach. The profile video is 7 minutes long, displaying various information about the Fish Market Depot which is then shared on social media YouTube, and Instagram. By making this profile video, it is hoped that it can provide information to the general public, especially the people of Sidoarjo.